Doubly latent multilevel analysis of the relationship among collective teacher efficacy, school support, and organizational commitment - Zhang, Zhonghua; Lee, John Chi-Kin; Yin, Hongbiao; Yang, Xin (Frontiers in Psychology, 2023)
Understanding the sources and the effects of collective teacher efficacy has been one of the central interests to many educational researchers and practitioners, because it is critical to understand how teachers can shape, and are shaped by, the educational processes in schools. Following the social cognitive perspective on the sources and consequences of efficacy beliefs, this study examined how school support influences collective teacher efficacy which in turn affects teachers’ organizational commitment. The participants included 969 teachers sampled from 28 primary and secondary schools in Hong Kong. To appropriately address the nature of collective teacher efficacy and school support as school-level variables, the doubly latent multilevel structural equation modeling approach was used to analyze the data. The results revealed the mediation mechanism played by collective teacher efficacy in explaining the effect of school support on teachers’ organizational commitment. Schools are suggested to consider fostering a supportive school environment as a strategy to improve teachers’ collective efficacy beliefs if it is wished to enhance teachers’ commitment to schools.